Deciphering indigenous bacteria in compacted bentonite through a novel and efficient DNA extraction method: Insights into biogeochemical processes within the Deep Geological Disposal of nuclear waste concept - Povedano-Priego, Cristina; Jroundi, Fadwa; Lopez-Fernandez, Margarita; Shrestha, Rojina; Spanek, Roman; Martín-Sánchez, Inés; Villar, María Victoria; Ševců, Alena; Dopson, Mark; Merroun, Mohamed L (Journal of hazardous materials, 2021)
Compacted bentonites are one of the best sealing and backfilling clays considered for use in Deep Geological Repositories of radioactive wastes. However, an in-depth understanding of their behavior after placement in the repository is required, including if the activity of indigenous microorganisms affects safety conditions. Here we provide an optimized phenol:chloroform based protocol that facilitates higher DNA-yields when other methods failed. To demonstrate the efficiency of this method, DNA was extracted from acetate-treated bentonites compacted at 1.5 and 1.7 g/cm3 densities after 24 months anoxic incubation. Among the 16S rRNA gene sequences identified, those most similar to taxa mediating biogeochemical sulfur cycling included sulfur oxidizing (e.g., Thiobacillus, and Sulfurimonas) and sulfate reducing (e.g., Desulfuromonas and Desulfosporosinus) bacteria. In addition, iron-cycling populations included iron oxidizing (e.g., Thiobacillus and Rhodobacter) plus reducing taxa (e.g., Geobacillus). Genera described for their capacity to utilize acetate as a carbon source were also detected such as Delftia and Stenotrophomonas. Lastly, microscopic analyses revealed pores and cracks that could host nanobacteria or spores. This study highlights the potential role of microbial driven biogeochemical processes in compacted bentonites and the effect of high compaction on microbial diversity in Deep Geological Repositories.
Keywords: Bentonite; radioaktivní odpad; Clay; RNA ribozomální 16S; Bacteria; bentonit; Radioactive Waste; jíl; RNA, Ribosomal, 16S